Pricing-to-market in a Ricardian model of international trade - Atkeson, Andrew 1961-; Burstein, Ariel T. 1974- (Working paper series / National Bureau of Economic Research, 2007)
We study the implications for international relative prices of a simple Ricardian model of international trade with imperfect competition and variable markups, providing a tractable account of firm-level and aggregate prices. We show that both trade costs and imperfect competition with variable markups are needed to account for pricing-to-market at the firm and aggregate levels. We also show that international trade costs are essential, but pricing-to-market is not, to account for a high volatility of tradeable consumer prices relative to the overall CPI-based real-exchange rate.